Towards acoustic monitoring of a mixed demersal fishery based on commercial data: The case of the Northern Demersal Scalefish Fishery (Western Australia) - Gastauer, S.; Scoulding, B.; Parsons, Miles (Elsevier BV, 2017)
© 2017 Elsevier B.V. Ongoing monitoring of complex, mixed species environments is a challenging task. In this study, the potential of acoustic and catch data collected aboard a commercial fishing vessel, in combination with geostatistical variance estimates, are explored as a means to derive information on the distribution and abundance of key species groups within selected fishing regions. The FV Carolina M, a trap fishing vessel which operates in waters off Broome, Western Australia, in the Northern Demersal Scalefish Fishery, was equipped with Simrad ES70 echosounders, operated at 38 and 120 kHz. Optical recordings of catch were also obtained, in addition to the acoustic data, during routine fishing operations in 2014. Three regions, where both optical and acoustic datasets were available, were selected for analysis. Geostatistical conditional simulations were used to combine acoustic density information with species composition proportions and length distributions w ithin the catch. For each of the input datasets 250 simulations were conducted, from which individual and combined sampling CVs were derived. Conversion of acoustic densities into abundance estimates was achieved through application of target strength to length relationships (TS-L). Where TS-L was unavailable in the literature for a particular species it was estimated through a Kirchhoff-ray mode model. TS-L equations were estimated for rankin cod (Epinephelus multinotatus)(TS RC  = 20 log 10 (L) - 79.6), triggerfish (Balistidae) (TS TF  = 20 log 10 (L) - 77.7) and spangled emperor (Lethrinus nebulosus) (TS SE  = 20 log 10 (L) - 70.8) at 38 kHz. Sampling error was found to be generally low for catch proportions ( < 12%) and acoustic densities ( < 10%). Total sampling error CV for species group abundances within each of the three regions was 9%–38%, which is similar to typical estimates reported for acoustic surveys.